Reliability and responsiveness of dynamic contrast-enhanced magnetic resonance imaging in rheumatoid arthritis. (March 2013) - Axelsen, MB; Poggenborg, RP; Stoltenberg, M; Kubassova, O; Boesen, M; Hørslev-Petersen, K; Bliddal, H; Hanson, LG; Østergaard, M
Abstract : Objectives: To investigate the responsiveness to treatment and the reliability of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in rheumatoid arthritis (RA) knee joints. Methods: DCE-MRI was performed in 12 clinically active RA knee joints before and 1, 7, 30, and 180 days after intra-articular injection with 80 mg methylprednisolone. Using semi-automated image processing software, DCE-MRI parameters, including the initial rate of enhancement (IRE) and maximal enhancement (ME), were generated for three regions of interest (ROIs): 'Whole slice', 'Quick ROI', and 'Precise ROI'. The smallest detectable difference (SDD), the smallest detectable change (SDC), and intra- and inter-reader intraclass correlation coefficients (ICCs) were used to assess the reliability of DCE-MRI. Responsiveness to treatment was assessed by the standardized response mean (SRM). Results: In all patients clinical remission of the knee was achieved at day 7. All DCE-MRI parameters decreased from day 0 to day 7. Using the Quick and Precise ROI methods, respectively, IRE decreased by 63% and 69%, ME decreased by 11% and 11%, Nvoxel decreased by 55% and 57%, and IRE × Nvoxel decreased by 84% and 85%. The intra- and inter-reader ICCs were very high (0.96–1.00). The decrease in DCE-MRI parameters was larger than the SDC for all patients. SRM was large for all parameters, ranging from –1.04 to –2.40. When the Whole slice ROI method was used, no parameters were responsive to treatment. Conclusions: DCE-MRI analysed using semi-automatic software is a reliable and responsive tool for assessing treatment in RA knees joints. Rough manual delineation of the joint to omit enhancement artefacts is necessary.